2013
DOI: 10.1016/j.fertnstert.2012.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment antimüllerian hormone levels determine rate of posttherapy ovarian reserve recovery: acute changes in ovarian reserve during and after chemotherapy

Abstract: Objective To identify factors associated with ovarian reserve (OR) impairment during and immediately after chemotherapy. Design Prospective cohort study. Setting Four university hospitals. Patients Adolescent and young adult females with a new diagnosis of cancer requiring chemotherapy. Interventions None. Main Outcome Measures Participants were followed to assess measures of OR (serum follicle-stimulating hormone, luteinizing hormone, estradiol, inhibin B, anti-mullerian hormone (AMH), and antral fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 22 publications
(31 reference statements)
2
82
0
3
Order By: Relevance
“…Earlier smaller studies have also reported lower amh levels in cancer survivors than in control subjects 15,[22][23][24][25][36][37][38][39] . In the subgroup of patients with regular menstrual cycles at the time of amh testing, factors with a significant positive effect on serum amh were younger attained age and regular menstrual cycles during chemotherapy; specifically, compared with no loss of menses during treatment, a history of losing and then regaining normal cycles predicted worse outcome.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Earlier smaller studies have also reported lower amh levels in cancer survivors than in control subjects 15,[22][23][24][25][36][37][38][39] . In the subgroup of patients with regular menstrual cycles at the time of amh testing, factors with a significant positive effect on serum amh were younger attained age and regular menstrual cycles during chemotherapy; specifically, compared with no loss of menses during treatment, a history of losing and then regaining normal cycles predicted worse outcome.…”
Section: Discussionmentioning
confidence: 80%
“…We did not have pretreatment measurements of serum amh, which could have been useful for comparison. Dillon et al 38 measured pre-and posttreatment serum amh in young female cancer survivors and demonstrated that pretreatment serum amh was significantly associated with posttreatment serum amh. Similar findings have been reported by other investigators [38][39][40][41][42] , demonstrating that, for patients with reduced ovarian reserve before treatment, chemotherapy moves them further toward a perimenopausal state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All measures of ovarian reserve demonstrated statistically significant changes during chemotherapy: alkylating agent exposure and baseline ovarian reserve were acutely associated with the magnitude of impairment. Particularly, pretreatment AMH levels were associated with the rate of recovery of AMH after treatment (Dillon et al 2013). …”
Section: Amh and Chemo-induced Gonadal Damage In Cancer Patientsmentioning
confidence: 99%
“…Recently, Dillon et al (2013) have evaluated factors (FSH, LH, E 2 , inhibin B, and AMH) associated with ovarian reserve impairment during and immediately after chemotherapy. All measures of ovarian reserve demonstrated statistically significant changes during chemotherapy: alkylating agent exposure and baseline ovarian reserve were acutely associated with the magnitude of impairment.…”
Section: Amh and Chemo-induced Gonadal Damage In Cancer Patientsmentioning
confidence: 99%